Novel recombinant proteins and peptides from Clonorchis sinensis and Opisthorchis viverrini for liver fluke exposure ELISA - Mohan, Sumathy; Natarajan, Mohan; Bruno, John G. (Biochemistry and biophysics reports, 2023)
Human serum samples from individuals living in Vietnam and Taiwan suspected of past Clonorchis sinensis or Opisthorchis viverrini infection were screened using several novel peptides and recombinant liver fluke proteins to determine if any consistent patterns could be discerned and used as the basis for future liver fluke ELISA development. Absorbance values at 405 nm were compared to those of pooled unexposed normal human serum and analyzed for statistical significance. The data exhibited some interesting patterns consistent with egg antigen sequestration in the gut possibly leading to lower serum antibody levels and potential regional exposure differences between Vietnamese and Taiwanese subjects. In particular, antibodies against Cathepsin B and B2 peptides, as well as a partial Cahedrin Domain peptide may be elevated in some Taiwanese serum samples while antibodies against recombinant Clonorchis egg protein and Hepatocellular Carcinoma Peptide Antigen 59 may be elevated in some samples from both Taiwan and Vietnam. The data appear to suggest that some of the novel recombinant protein and peptide antigens selected and tested herein warrant further study with larger sample sizes as possible targets for detecting anti-liver fluke antibodies by ELISA from humans suspected of liver fluke infections. •Six different novel recombinant liver fluke proteins or peptides were screened for exposure ELISA potential.•Some of the novel targets reacted against human serum samples from Taiwan and Vietnam.•A recombinant partial Cs44 protein did not react with serum samples perhaps due to a missing or hidden epitope.•A Clonorchis egg protein did not react strongly with sera perhaps due to egg sequestration in the gut.